Total nutrient digestibility and small intestine starch digestion in Nellore and Angus young bulls fed a whole shelled corn diet. Issue 1 (28th November 2018) - Carvalho, José Rodolfo R.; Schoonmaker, Jon P.; Chizzotti, Mario L.; Teixeira, Priscilla D.; Dias, Julio Cesar O.; Gionbelli, Tathyane R. S.; Rodrigues, Aline C.; Costa, Suely F.; Ladeira, Marcio M.
Abstract: Eighteen Nellore and 18 Angus young bulls with BW of 381 ± 12 kg were randomly assigned into two feeding groups (whole shelled corn [WSC] or ground corn with silage [GC]) to evaluate the interaction of breed and diet on total nutrient digestibility, pancreatic α‐amylase, and maltase activity and SLC5A1 expression in the small intestine. Experimental diets (DM basis) included (a) a diet containing 30% corn silage and 70% GC and soya bean meal‐based concentrate and (b) a diet containing 85% WSC and 15% of a soya bean meal‐ and mineral‐based pelleted supplement. The treatments were Nellore fed GC diet; Nellore fed WSC diet; Angus fed GC diet; and Angus fed WSC diet. Total faecal collection for the digestibility trial occurred from day 48 until day 50 of the experimental period. Feeding the WSC diet reduced DM and NDF intake ( p < 0.01). Angus had greater DM and nutrient intake in kg/day ( p < 0.01). However, there was no breed effect on DM and nutrient intakes based on percentage of BW ( p > 0.19). Angus had greater starch digestibility ( p = 0.03) than Nellore. Cattle fed the WSC diet had greater DM, NDF and starch digestibility ( p < 0.01) compared with those fed the GC diet. The activity of pancreatic α‐amylase (U/g of protein) was greater in Nellore ( p < 0.01) and was not affected by diet ( p = 0.52). In duodenum, maltase activity (U/g of protein) was greater in bulls fed GC diet ( p = 0.02). Expression of the gene SLC5A1 was not affected by breed or diet ( p > 0.05). In conclusion, Nellore had less capacity to digest starch. However, they did not have less pancreatic α‐amylase and duodenal maltase activity compared to Angus. The use of the WSC diet increases DM and total nutrient digestibility.